adding -2x+6
3y=-2x+6
dividing by 3
y=(-2/3)x+(6/3)
=(-2/3)x+2
if you want to make y the subject
however ifyou want to make 'x' the subject
adding -3y+6
2x=-3y+6
dividing by 2
x=(-3/2)y+(6/2)
=(-3/2)y+3
2006-12-05 04:22:41
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
I'll guess this equation refers to a straight line and the answer you need is having it rearranged to the usual form for one. Since that form is always: y = ax + b, we have to move every term (part) without "y" in it to the right side so we subtract "2x" and "-6" from both sides: 2x - 2x + 3y - 6 - (-6) = 0 - 2x - (-6). The 2x - 2x is zero and -6 - (-6) (or - 6 + 6, if you like) is also zero so we get: 0 + 3y + 0 = -2x + 6 or: 3y = -2x + 6. Last step is to divide both sides by 3 to get just 1y on the left side: 3y/3 = -2x/3 + 6/3 or: y = –2/3 x + 2 (in case that makes it hard to read without characters for fractions, it is –2x divided by 3 (–2/3 x = –.667x); it is NOT –2 divided by 3x!)
2006-12-05 12:08:56
·
answer #2
·
answered by roynburton 5
·
1⤊
0⤋
Add 6 to both sides
2x + 3y -6 +6 = 0+6
2x +3y =6
2x+3y - 3y = 6 - 3y
2x = 6 - 3y
The important thing is that the equality sign means that both sides are equal - what you do to one side you must do to the other.
2006-12-05 11:56:58
·
answer #3
·
answered by poohead120b 1
·
1⤊
0⤋
2x plus 3y -6=o
2x plus 3y=6
just change the place of the 6 on the right hand side and you must change the sign// (its so simple man are you in 5th class or what??/
2006-12-05 11:57:09
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
y = -2/3 x +2= 2 (x/3 -1)
2006-12-05 11:56:15
·
answer #5
·
answered by maussy 7
·
0⤊
0⤋
2x + 3y = 6
3y = 6 - 2x
y = 2 - (2x)/3
2006-12-05 11:56:32
·
answer #6
·
answered by draco_mortifer 2
·
0⤊
0⤋